2021
DOI: 10.1038/s41598-021-91817-9
|View full text |Cite
|
Sign up to set email alerts
|

Design and in silico validation of polymerase chain reaction primers to detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)

Abstract: Accurate designing of polymerase chain reaction (PCR) primers targeting conserved segments in viral genomes is desirable for preventing false-negative results and decreasing the need for standardization across different PCR protocols. In this work, we designed and described a set of primers and probes targeting conserved regions identified from a multiple sequence alignment of 2341 Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) genomes from the Global Initiative on Sharing All Influenza Data (GIS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The targeted RdRp, S, and N genes with specifications were shown in Table 1, while Figure 5 was used to illustrate the associated histograms. These results showed that some of the primer parameters and probes listed in the previous studies of Li et al (2020) and Davi et al (2021) should be enhanced. They also indicated that the sets used in this study did not have secondary structures.…”
Section: Primer Designmentioning
confidence: 65%
“…The targeted RdRp, S, and N genes with specifications were shown in Table 1, while Figure 5 was used to illustrate the associated histograms. These results showed that some of the primer parameters and probes listed in the previous studies of Li et al (2020) and Davi et al (2021) should be enhanced. They also indicated that the sets used in this study did not have secondary structures.…”
Section: Primer Designmentioning
confidence: 65%
“…Considering Davi et al . ( 2021 ) reported that a supercomputer was required for the alignment of only 2,341 full viral genome sequences using Clustal Omega, ViralMSA would be the best choice for a PC-level computer. When the MAFFT (Katoh and Standley 2013 ) v7.490 program was used with the FFT-NS-2 option, it took more than 3 days to complete the alignment on the same computer.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, CS ‘candidates’ would be the correct term to describe the output of post-MSA process and its manipulation. Running trimAl with the ‘-automated1’ option (a heuristic trimming method), as described previously (Davi et al 2021 ), discarded only a few sites from the original alignments and generated six subsequences covering 29,384 bp of the original 29,903 bp, suggesting that parameter optimization was required. However, as a single-threaded program, the prolonged execution time for a typical trimAl run (~ 16 h) made it unfeasible to tweak the parameters to prioritize conserved sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDC in the US also obtains the emergency use authorization (EUA) from FDA (Food and Drug Administration) for the first RT-PCR test. During the epidemic, a growing number of commercial kits for detecting SARS-CoV-2 and its variations were created, which were then employed in clinical laboratories and other organizations [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%